IMPLEMENTASI MANAJEMEN PEMBINAAN AKHLAK DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA KELAS V PADA KEGIATAN HARI SABTU - Sofiyulloh; Lailatul Karisma (BAMALA Institute, 2026)
Religious education and moral development play an important role in shaping the religious character of students in Islamic elementary schools. Although MI NU Raden Rahmat 95 has implemented various moral development and religious habituation programs, the religious character of fifth-grade students has not developed optimally due to the presence of undisciplined behavior, impoliteness, and low appreciation of religious values ​​in daily life. This study aims to determine the planning, implementation, and obstacles to moral development through Saturday activities at school. The study used a qualitative approach with a case study type. Data were obtained through observation, interviews, and documentation. The results showed that moral development has been planned and implemented systematically through religious habits, teacher role models, and routine religious activities. However, its implementation still faces obstacles such as lack of student awareness, the influence of family and peer environments, the use of technology, and monotonous learning methods so that the formation of students' religious character has not run optimally.